(untitled) (Transport systems and technologies, 2022)
The paper presents the results of the analysis of surface defects and faults of freight car wheels caused by frictional interaction with composite brake pads. It is established that the main influence on the thermomechanical behavior of freight car wheels is caused by thermal loads that occur during braking. In cases of thermal overloads, which arise mainly as a result of prolonged braking, the generation of stresses and deformations occurs, the consequences of which are the appearance of high-temperature local defects on the rolling surface of freight car wheels. These defects negatively affect the safety of trains and significantly increase the operating costs of railway transport. To determine the thermal stress state of the freight car wheel during braking, its calculation was carried out. As a calculation method, the finite element method was used, which is implemented in the SolidWorks Simulation software package. The temperature effect on the wheel during braking is determined to be permissible from the point of view of ensuring the strength of the wheel. The conducted research will contribute to the creation of recommendations for managing the temperature effect on the wheel, as well as improving the safety of trains and significantly reducing operating costs in railway transport.